Case series of Foley’s induction in patients with previous caesarean - R., Hemalatha K.; D., Swetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objective of this study was to study the efficacy of intracervical Foley’s catheter induction in women with previous history of caesarean section and to evaluate the maternal and fetal outcome of these pregnancies. Methods: It is a prospective analysis of 30 patients whose labour was induced by intracervical Foley’s bulb for VBAC delivery. This study was conducted in KIMS, Hubli. Age, parity, indication of previous caesarean, inter-pregnancy interval and outcome of index pregnancy were studied in detail and analysed. Results: 30 women with previous history of caesarean were included into the study. Various indications of induction during index pregnancies were- post-datism, IUGR, intra-uterine foetal demise and severe pre-eclampsia and eclampsia. Out of 30 women, 18 (60%) had successful VBAC delivery, 12 (40%) underwent repeat LSCS. 19 cases needed augmentation of labour. Indications for caesarean section were failed induction in 5 (16.6%) women, threatened scar rupture in 3 (10%), non-progress of labour in 2 (6.6%) and meconium stained amniotic fluid in 2 (6.6%). No cases of uterine rupture or maternal mortality was noted in the study. Conclusions: In our study the rate of vaginal birth was 60% without major maternal complications. Hence intracervical Foley’s catheter is an effective, safe and acceptable for labour induction in women with previous caesarean.